Dentinal tubule occlusion using Er:YAG Laser: an in vitro study - Hongmin ZHUANG; Yuee LIANG; Shaowen XIANG; Huanying LI; Xingzhu DAI; Wanghong ZHAO (University of São Paulo, 2021)
Abstract Objectives We analyzed the effects of the Er:YAG laser used with different parameters on dentinal tubule (DT) occlusion, intrapulpal temperature and pulp tissue morphology in order to determine the optimal parameters for treating dentin hypersensitivity. Methodology Dentin specimens prepared from 36 extracted human third molars were randomized into six groups according to the treatment method (n=6 each): control (A); Gluma desensitizer (B); and Er:YAG laser treatment at 0.5 W , 167 J/cm2 (50 mJ, 10 Hz) (C), 1 W , 334 J/cm2 (50 mJ, 20 Hz) (D), 2 W , 668 J/cm2 (100 mJ, 20 Hz) (E), and 4 W and 1336 J/cm2 (200 mJ, 20 Hz) (F). Treatment-induced morphological changes of the dentin surfaces were assessed using scanning electron microscopy (SEM) to find parameters showing optimal dentin tubule occluding efficacy. To further verify the safety of these parameters (0.5 W, 167 J/cm2), intrapulpal temperature changes were recorded during laser irradiation, and morphological alterations of the dental pulp tissue were observed with an upright microscope. Results Er:YAG laser irradiation at 0.5 W (167 J/cm2) were found to be superior in DT occlusion, with an exposure rate significantly lower than those in the other groups (P<0.05). Intrapulpal temperature changes induced by Er:YAG laser irradiation at 0.5 W (167 J/cm2) with (G) and without (H) water and air cooling were demonstrated to be below the threshold. Also, no significant morphological alterations of the pulp and odontoblasts were observed after irradiation. Conclusion Therefore, 0.5 W (167 J/cm2) is a suitable parameter for Er:YAG laser to occlude DTs, and it is safe to the pulp tissue.